The therapeutic effect of hesperetin on doxorubicin-induced testicular toxicity: Potential roles of the mechanistic target of rapamycin kinase (mTOR) and dynamin-related protein 1 (DRP1) - Tektemur, Ahmet; Tektemur, Nalan Kaya; Guezel, Elif Erdem (Academic Press Inc Elsevier Science, 2022)
Clinical utilization of doxorubicin (DOX), which is a commonly used chemotherapeutic, is restricted due to toxic effects on various tissues. Using hesperetin (HST), an antioxidant used in Chinese traditional medicine protects testis against DOX-induced toxicity although the molecular mechanisms are not well-known. The study was aimed to examine the possible role of the mechanistic target of rapamycin kinase (mTOR) and dynamin 1-like dynamin-related protein 1 (DRP1) in the therapeutic effects of HST on the DOX-induced testicular toxicity. Rats were divided into Control, DOX, DOX + HST, and HST groups (n = 7). Single-dose DOX (15 mg/kg) was administered intraperitoneally and HST (50 mg/kg) was administered by oral gavage every other day for 28 days. Total antioxidant status (TAS), histopathological evaluations, immunohistochemistry, and gene expression level detection analyses were performed. Histopathologically, DOX-induced testicular damage was ameliorated by HST treatment. DOX reduced testicular TAS levels and increased oxidative stress markers, 8-Hydroxy-deoxyguanosine (8-OHdG), and 4-Hydroxynonenal (4-HNE). Also, upregulated mTOR and DRP1 expressions with DOX exposure were decreased after HST treatment in the testis (p < 0.05). On the other hand, DOX-administration downregulated miR-150-5p and miR-181b-2-3p miRNAs, targeting mTOR and mRNA levels of beclin 1 (BECN1) and autophagy-related 5 (ATG5), autophagic markers. Furthermore, these levels were nearly similar to control testis samples in the DOX + HST group (p < 0.05). The study demonstrated that HST may have a therapeutic effect on DOX-induced testicular toxicity by removing reactive oxygen species (ROS) and by modulating the mTOR and DRP1 expressions, which have a critical role in regulating the balance of generation/elimination of ROS.
Keywords: Doxorubicin; DRP1; Hesperetin; mTOR; Testis